Lipopeptides from the Tropical Marine Cyanobacterium Symploca sp. - Mevers, Emily (American Chemical Society and American Society of Pharmacognosy, 2014)
[Image: see text] A collection of the tropical marine cyanobacterium Symploca sp., collected near Kimbe Bay, Papua New Guinea, previously yielded several new metabolites including kimbeamides A–C, kimbelactone A, and tasihalide C. Investigations into a more polar cytotoxic fraction yielded three new lipopeptides, tasiamides C–E (1–3). The planar structures were deduced by 2D NMR spectroscopy and tandem mass spectrometry, and their absolute configurations were determined by a combination of Marfey’s and chiral-phase GC-MS analysis. These new metabolites are similar to several previously isolated compounds, including tasiamide (4), grassystatins (5, 6), and symplocin A, all of which were isolated from similar filamentous marine cyanobacteria.